Astronomické omyly provázející pražský orloj - Křížek, M. (Michal); Křížek, P.; Šolc, J. (2010)
The upper dial-plate of the astronomical clock is an astrolabe controlled by a clockwork mechanism. It represents a stereographic projection of the celestial sphere from its North Pole onto the tangent plane passing through the South Pole. We give a survey of several astronomical mistakes that appeared on this dial throughout centuries.